Climate Change, Poverty and Income Inequality Linkage: Empirical Evidence from Nigeria - Ogbeide-Osaretin, Evelyn Nwamaka; Orhewere, Bright; Ebhote, Oseremen; Akhor, Sadiq Oshoke; Imide, Israel. O. (International Journal of Energy Economics and Policy, 2022)
There seems to be a vicious cycle between climate change and income inequality. Hence, this study examined the existence of a feedback relationship between climate change and income inequality in Nigeria. The study employed an annual data series for the period from 1980 to 2020. Income inequality was measured by Gini while climate change was captured by temperature. The upshot of the study revealed that there is a feedback substantial connectivity between climate change and income inequality. The impact of climate change on income inequality conformed to the U-shaped hypothesis. Other factors of climate change were population growth, economic development, and emission of carbon dioxide. Hence, the study pertinently advocates and recommends effective population control, reduction of income inequality through the provision of employment and education, and the supply of modern and efficient energy in the purse of economic growth and development.